The Effect Of Work Motivation, Spiritual Leadership, And Organizational Culture On The Work Achievement Of Yogyakarta Social Office Office Employees - Theofilus Eko Putra Anjur; Ignatius Soni Kurniawan (Jurnal Ilmu Manajemen Profitability, 2022)
The purpose of this study was to determine the effect of work motivation, spiritual leadership, and organizational culture on employee performance at Kantor Dinas Sosial Kota Yogyakarta. The method used in this study is a quantitative method using multiple linear regression statistical analysis to analyze the effect of the independent variable on the dependent variable in the study. The population in this study were all employees at Kantor Dinas sosial Kota Yogyakarta, with a sample size of 58 respondents. The results of this study indicate that work motivation, spiritual leadership, and organizational culture have a positive and significant influence on employee performance